Oral uracil and tegafur as postoperative adjuvant metronomic chemotherapy in patients with advanced oral squamous cell carcinoma - Jiun-Sheng Lin; Chieh-Yuan Cheng; Chung-Ji Liu (Elsevier, 2015)
Background/purpose: In this study, we evaluated the effectiveness of oral uracil-tegafur (UFUR) as a postoperative adjuvant treatment for patients with advanced oral squamous cell carcinoma (OSCC). Materials and methods: The study cohort consisted 80 patients with advance cancer treated between January 2003 and December 2007. Half of the patients received oral UFUR as postoperative metronomic adjuvant chemotherapy, while the other half received no treatment. No patients received postoperative radiotherapy or other systemic chemotherapy. Disease-free survival and toxicity were evaluated in these two groups. Twenty-two patients were assessed pre- and postoperatively for viable circulating endothelial progenitor cells using flow cytometry. Results: The disease-free survival rates at 4 years were 84.6% with oral UFUR treatment and 60.9% without UFUR therapy (P = 0.02). The toxicity and disease progression profiles did not differ significantly between the two groups, but viable circulating endothelial progenitor cell counts decreased after the administration of oral UFUR. Advanced OSCC patients who received oral UFUR had a better prognosis than those who did not. Conclusion: Oral UFUR is a promising postoperative metronomic adjuvant chemotherapy regimen for advanced OSCC.